2018
DOI: 10.3389/fphys.2018.00770
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Physical Profile of Snowboarding: A Preliminary Review

Abstract: The sport of snowboarding has grown in popularity as both a recreational winter activity as well as a prominent Olympic sport. Both forms are comprised of one of three different disciplines within the sport: freestyle, alpine, and snowboard-cross. In recent years, the increased professionalism and substantial growth of snowboarding as a global sport has increasingly attracted the interest of exercise physiologists and sport scientists. Given the small (but growing) number of studies that have been published, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…From the perspective of physical recovery, the interrelationship and interaction between aerobic and anaerobic capacities of snowboarding athletes is also a hot research topic. Vernillo et al (38) found that the correlation between maximal oxygen uptake (V̇ o 2 max) and performance of elite snowboarding athletes in the parallel giant slalom, parallel slalom, and snowboard cross events is low and not statistically significant ( p > 0.05). In contrast, peak aerobic power output was highly correlated with the performance of elite snowboarding athletes in men's parallel slalom, giant slalom, and snowboard cross, ( r = −0.92, r = −0.88, r = −0.93, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of physical recovery, the interrelationship and interaction between aerobic and anaerobic capacities of snowboarding athletes is also a hot research topic. Vernillo et al (38) found that the correlation between maximal oxygen uptake (V̇ o 2 max) and performance of elite snowboarding athletes in the parallel giant slalom, parallel slalom, and snowboard cross events is low and not statistically significant ( p > 0.05). In contrast, peak aerobic power output was highly correlated with the performance of elite snowboarding athletes in men's parallel slalom, giant slalom, and snowboard cross, ( r = −0.92, r = −0.88, r = −0.93, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Platzer et al (27) found a strong correlation ( r = 0.67) between lower-body leg power (4.46–6.54 W/kg) and World Cup points in women alpine and snowboard cross snowboarding athletes. Another study on lower extremity isometric muscle strength also reported that the maximal isometric voluntary contraction (MVC) of the knee extensor muscles in elite male snowboard cross (680.1 ± 76.8 N·m), parallel slalom, and giant slalom (731.9 ± 181.9 N·m) snowboarding athletes was highly correlated with performance ( r = −0.93, r = −0.94, r = −0.97) (38). It suggests that snowboarding athletes with greater lower-body muscle strength and power would be at an advantage during the competitions.…”
Section: Resultsmentioning
confidence: 99%
“…Para alpine skiing and snowboard are technical sports, which place high demands on the athlete’s technical skill, balance and motor control 12 13. In addition, these sports challenge the athlete’s strength, power, aerobic and anaerobic capacity 12 13.…”
Section: Sport-specific Demandsmentioning
confidence: 99%
“…Para alpine skiing and snowboard are technical sports, which place high demands on the athlete’s technical skill, balance and motor control 12 13. In addition, these sports challenge the athlete’s strength, power, aerobic and anaerobic capacity 12 13. The demands of Para snowboarding athletes and Para alpine skiers that compete in the categories for standing or visually impaired athletes are similar to their able-bodied counterparts 14.…”
Section: Sport-specific Demandsmentioning
confidence: 99%
“…Snowboarding is a young sport, which has evolved rapidly during the last 30 to 40 years, with the first modern-style boards produced in the early 1970s and first showcased in the Winter Olympics at Nagano in 1998 (Vernillo, Pisoni, & Thiébat, 2018).…”
Section: Introductionmentioning
confidence: 99%